Future scenarios for the fruit and vegetable production and supply chain in the department of Valle del Cauca, 2019 horizon - Betancourt - Guerrero, Benjamin; Scarpetta Calero, Gildardo (Cuadernos de Administración, 2017)
This article presents the methodology, discussion, and results of the research project entitled “Analysis and Development of Future Scenarios for the Valle of Cauca Fruit and Vegetable Growing Chain for the 2019 Horizon”. The purpose is manifold: 1. Identifying the probable and possible future scenarios for the Valle of Cauca fruit and vegetable growing chain, applying for its analysis prospective methodologies recognized by the academic community and by the fruit and vegetable growers interested in the topic; 2. From the identified scenarios: trendential, optimistic and pessimistic, the Betting Scenario to which the sector’s actions of improvement must be oriented is defined; 3. To accomplish this, strategic guidelines are included in the betting scenario. Experts suggest that fruit and vegetable growers will define their projects and the strategies that would enable Valle del Cauca to improve its competitiveness in the sector, creating a positive impact on the region as well as increasing its exports; 4. The aforementioned is being supported by Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA, for its name in Portuguese) that uses technological prospective and involves other connected fields of knowledge. Its focus is to discover the technical and social issues affecting an agricultural productive chain using technology as a tool that provides solutions to the community or social groups that are part of the productive chain; 5. This analysis was done in two phases: diagnostic and prospective. In the diagnostic phase, the documental analysis and the consultation with growers, producers, and experts were carried out. In the prospective phase, consultation with experts and tools such as brain storming, the Regnier Abacus, and multi-criteria analysis were applied. For the scenarios design, the morphological analysis was applied.